The Semiotic Interpretation of Joan Miro’s World of Signs - Matevosyan, Armine; Hovakimian, Nazeny (Armenian Folia Anglistika, 2014)
The following article is devoted to the semiotic interpretation of some paintings by an outstanding Catalonian artist, Joan Miro. Here an attempt is made to concentrate on the symbolic objects, the colours and the whole mood of Miro’s paintings, as well as to the emotional state of the artist himself, his descriptions of his art to bring out the link between linguistic and artistic signs.
Keywords: semiotics; sign; art; visual language; interpretation